The Memory of Pain. : Women's Testimonies of the Holocaust. - Loew, Camila (Value Inquiry Book Series, 237., 2011)
In this book, Camila Loew analyzes four women's testimonial literary writings on the Holocaust to examine and question some of the tenets of the fields of Holocaust studies, gender studies, and testimony. Through a close reading of the works of Charlotte Delbo, Margarete Buber-Neumann, Ruth Klüger, and Marguerite Duras, Loew foregrounds these authors' search for a written form to engage with their experiences of the extreme. Although each chapter contains its individual focus and features, the book possesses a unity in intention, concerns, and consequences. In the theoretical introduction that.